ANTI-INFLAMMATORY, ANTIOXIDANT, AND SELECTIVE ANTIBACTERIAL EFFECTS OF EUADENIA EMINENS ROOT BARK. - Dickson, R A; Fleischer, T C; Komlaga, G; Komlaga, G (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Euadenia eminens Hook f. (Capparaceae) has traditional uses in the management of conjunctivitis, iritis, ophthalmia, tuberculosis, otalgia and rectal prolapse. The fruit pulp is also eaten as an aphrodisiac. In this paper, we report on the anti-inflammatory, antioxidant and antibacterial effects of its roots. A 70 % ethanol extract was tested for anti-inflammatory effect using the carrageenan-induced oedema in chicks. Free radical scavenging, total antioxidant and total phenol content were assessed spectrophotometrically. The extract was tested for antibacterial activity using the agar well diffusion method and micro dilution assays. The 70% ethanol extract gave a maximal inhibition of oedema by 74.18 % at 30 mg/kg. The total antioxidant capacity expressed in terms of ascorbic acid was 0.609 mg/g dry weight. The total phenol in terms of tannic acid was 7.25 mg/g dry weight. The extract also demonstrated free radical scavenging activity yielding IC50 value of 1.175 mg/mL. The root extract however, showed selective antibacterial activity, inhibiting growth of two microorganisms; Bacillus subtilis and Bacillus thurigiensis. The MICs were 500 and 1000 µg/mL respectively. These results may account in part for the ethnopharmacological use of the plant.